Research on the evolution and improvement of China’s shadow education governance policy from the perspective of multiple streams theory - Xiang, Kemi; Liu, Jinsi; Chen, Xinzhong; Zhang, Anlu (Frontiers in Psychology, 2023)
From a global perspective, after-school tutoring education, also known as shadow education, has developed rapidly at the beginning of this century, but shadow education has also brought many practical problems, such as the increased burden on parents and children, and the unfairness of education. At present, the Chinese government is vigorously implementing the double reduction policy, and has achieved remarkable practical results. Then, this paper focuses on the evolution of the government policy of shadow education in China. First of all, this paper analyzes the four stages of shadow education governance policy experience: the acquiescent survival stage, the encouraging development stage, the preliminary regulation stage and the comprehensive rectification stage. In addition, Python was used to conduct text mining for policies in different periods, and analyze the focus of policies in different stages by obtaining high-frequency vocabulary. Then, this paper uses the multiple streams theory to explore its evolution process and change mechanism. Finally, we put forward corresponding countermeasures for the lack of current shadow education governance policies. The study found that the objects, scope of adjustment, and protection of rights and interests of China's shadow education governance policies have undergone significant changes in the periodical changes. Through the constant interaction, brewing, and interweaving of the stream of problems, the stream of politics, and the stream of policy, the window of opportunity for policy change was jointly promoted. The innovations of this paper mainly include: First, the author systematically combs the evolution of China's shadow education governance policies, and uses text mining methods to compare the differences of governance policies at different stages; Second, multiple streams theory was used as the theoretical framework to analyze the reasons for the focus of shadow education governance policy changes.